Rapid along-strike variations of shallow crustal structure in response to Indo-Burma subduction: constraints from multi-type passive seismic data - Bai, Yiming (2023)
Characteristics of the subducting crust and the attached sedimentary cover play a key role in shaping the structure and processes in the hanging wall of a convergent plate boundary. Such influence must be significant in the oblique Indo-Burma subduction zone. Yet, the poorly resolved shallow crustal velocity structure of the overriding Burma plate, especially its lateral variation along the subduction margin, hinders a comprehensive understanding of the Indo-Burma subduction dynamics. Here, we take advantage of the new and dense broadband seismic data in Myanmar to image the regional S-wave velocity (Vs) structure in the top 10 km of crust by joint inversion of Rayleigh-wave ellipticity, receiver function and P-wave polarization. The new velocity model not only matches surface geology and seismic reflection profiles, but also reveals new and rapidly varying near-surface features, including (1) the exhumed high-velocity metamorphic belt of the Indo-Burma accretionary prism, which is more prominent in the south with a shallower depth extent and greater Vs of ∼3.5 km/s; and (2) contrasting Vs structure beneath the two Quaternary volcanoes, that is, Vs of typical crystallized igneous rocks (∼3 km/s) beneath Monywa versus Vs slower than the adjacent basin sediments (<2.5 km/s) under Mt. Popa. Combining with existing knowledge, we propose that the observed along-strike changes in the shallow forearc structure could be attributed to the northward increase of the off-scraped/underplated Ganges-derived Bengal sediments in the inner accretionary prism and the uneven distribution of the sediment-derived fluids, the majority of which may be trapped within the prism in the north but be subducted to deeper sub-arc level in the south. These eventually result in slower exhumation of the metamorphic belt and less active shallow crustal magmatism in the north than the south. Further, we speculate that the Bengal sediment behavior and the upper plate crustal structure might be modulated by a transition of the incoming Indian plate from the continental lithosphere beneath Tibet and northern Myanmar to thin continental/oceanic nature in the south.